1963
DOI: 10.1083/jcb.19.2.285
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics of Intestinal Epithelia in the Rat Two Months After Partial Resection of the Ileum

Abstract: Sprague-Dawley rats that had been subjected 2 months previously to partial resection (10 per cent) of thc small intestine and an equal number of control rats were injected with tritiated thymidine and sacrificcd at intervals during the subsequent 16 hours. Segments of duodenum, jejunum and ileum were prestained by the Feulgen technique and radioautographed. ~fhe proportion of crypt cells bearing labeled nuclei, the perccntage of labeled crypt cells in mitosis and the appearance of labeled crypt ceils on the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
3

Year Published

1967
1967
1990
1990

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(52 citation statements)
references
References 6 publications
4
45
0
3
Order By: Relevance
“…Similarly, others have shown that postoperatively increases in the heights of ileal villi greatly exceed those of jejunal villi (13). By contrast, studies of crypt cell kinetics after resection show almost identical responses proximally and distally (11,12). This suggests that cell turnover in the crypts is controlled by mechanisms different from those regulating the villi.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, others have shown that postoperatively increases in the heights of ileal villi greatly exceed those of jejunal villi (13). By contrast, studies of crypt cell kinetics after resection show almost identical responses proximally and distally (11,12). This suggests that cell turnover in the crypts is controlled by mechanisms different from those regulating the villi.…”
Section: Discussionmentioning
confidence: 99%
“…Regional variations in mucosal enzymne concentrations also highlight the need for careful standardization of the segments being studied. In the present experiments all of these factors were matched in control and resected animals and therefore it seems reasonable to attribute the observed effects to the resection per se; however the possibility remains that endogenously synthesized steroid or other hormones played a part in the production of the observed effects (11,36,37), especially since the known changes in cell kinetics also occur in the unresected members of paired parabiotic rats (36).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a dissociation between the mor phological, enzymatic and transport changes following resection [64,65]. Why might changes in intestinal structure and function occur independently rather than in concert?…”
Section: Patterns and Mechanisms Of Adaptation Of Intestinal Transportmentioning
confidence: 99%